Association of 3-year change in frailty index with risk of all-cause mortality among older Chinese population: a national cohort study - Dechen Liu; Qianqian Ma; Mingyu Zuo; Yuqi Niu; Jinjin Wang; Guoli Yan (BMC Geriatrics)
Abstract Background Evidence on the association of dynamic change in frailty index (FI) with risk of all-cause mortality in the older Chinese population is limited. This study aimed to explore the association of 3-year change in FI with risk of all-cause mortality in an older Chinese population. Methods We analyzed the data of 4969 participants from the Chinese Longitudinal Healthy Longevity Survey. The primary outcome was all-cause mortality, which was a binary variable and defined as completed data and censored data. Cox proportional-hazard models were used to assess the association of 3-year change in FI with risk of all-cause mortality by using hazard ratios (HRs) and 95% confidence intervals (CIs). Subgroup analyses were conducted to explore the association of 3-year change in FI with risk of all-cause mortality. Additionally, a restricted cubic spline analysis was also conducted to describe the dose-response association. Results During a median of 4.08 years of follow-up, deaths were observed in 1388 participants. We observed a 1.27-fold higher risk of all-cause mortality with increase in FI ≥ 0.045 versus change in FI < 0.015 (HR = 2.27, 95% CI: 1.89–2.73). Similar significant associations were observed in the subgroup analyses by age, sex, and residence at baseline. Additionally, a nonlinear dose-response association of 3-year change in FI with risk of all-cause mortality was observed (P overall < 0.001 and P nonlinear < 0.001). Conclusions Excessive increase in FI was positively associated with an increased risk for all-cause mortality. Approaches to reducing FI may be of great significance in improving the health of older Chinese individuals.